Effect of Preoperative Thoracic Paravertebral Blocks on Emergence Agitation During Tracheal Extubation: A Randomized Controlled Trial - Liu, Wei; Luo, Taijun; Wang, Fei; Zhang, Ding; Liu, Tao; Huang, Jiapeng; Xu, Shaofa (Frontiers in Medicine, 2022)
Objective: To compare the effects of preoperative thoracic paravertebral blocks (TPVB) with intercoastal nerve blocks (ICNB) on emergence agitation (EA) during tracheal extubation in patients underwent thoracoscopic lobectomy. Design, Setting, and Participants: A randomized clinical trial was conducted in patients undergoing thoracoscopic lobectomy at Beijing Chest Hospital between June 2019 and December 2020. Interventions: Patients were randomly assigned 1:1 to receive either ultrasound-guided preoperative TPVB or ICNB. Main outcomes and Measures: The primary outcome was the occurrence of emergency agitation, which was evaluated by Aono’s four-point scale (AFPS). Secondary outcomes included hemodynamics [mean arterial pressure (MAP) and heart rate (HR)]; and postoperative pain intensity [visual analogue scale (VAS), Ramsay sedation score (RSS), and patient-controlled analgesia (PCA) demand times]. Results: Among the 100 patients aged 55-75 years old, 50 were randomized to each group; Ninety-seven patients completed the trial. Compared to the ICNB group, the occurrence of EA in TPVB group was significantly lower [31.3% (15/48) vs. 12.2% (6/49), relative risk = 1.276, 95% CI: 1.02 ~ 1.60, P = 0.028]. For patients in TPVB group, the MAP and HR at 5 minutes, 10 minutes, 30 minutes after extubation were significantly lower; the intraoperative details included emergence time, extubation time, and consumption of sufentanil were significantly shorter than that in ICNB group. Additionally, patients in TPVB group showed significantly lower VAS at rest or coughing and significantly lower RSS at 60 min and 240 min after extubation than patients in ICNB group (all P < 0.05). Conclusions: Preoperative TPVB was associated with less emergence agitation during tracheal extubation when compared with ICNB in patients undergoing thoracoscopic lobectomy. Trial Registration: The study protocol was registered at the Chinese Clinical Trial Registry (ChiCTR1900023852). URL: http://www.chictr.org.cn/index.aspx